2017
DOI: 10.1007/s00127-017-1340-x
|View full text |Cite
|
Sign up to set email alerts
|

The Occupy Central (Umbrella) movement and mental health distress in the Hong Kong general public: political movements and concerns as potential structural risk factors of population mental health

Abstract: Many citizens participated in the movement, which was led by youths and might have increased the general public's mental distress. Negative personal responses to the movement and emotions toward political situations were potential risk factors. As the political tension would last and political pessimism is globally found, politics may have become a regular and persistent structural risk factor negatively affecting population mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…Extensive use of riot-control measures including physical force, tear gas, rubber bullets and beanbag rounds has been described as one of the worst humanitarian crisis Hong Kong has ever experienced. 2 Previous population-representative research has identified an increased prevalence of depression during and following pro-democracy movements 3–5 relative to periods without significant social or political dispute or upheaval. 6 7 Research has also shown that such population-wide movements or conflicts impact the mental health of the entire population, even including those who are not directly involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive use of riot-control measures including physical force, tear gas, rubber bullets and beanbag rounds has been described as one of the worst humanitarian crisis Hong Kong has ever experienced. 2 Previous population-representative research has identified an increased prevalence of depression during and following pro-democracy movements 3–5 relative to periods without significant social or political dispute or upheaval. 6 7 Research has also shown that such population-wide movements or conflicts impact the mental health of the entire population, even including those who are not directly involved.…”
Section: Introductionmentioning
confidence: 99%
“…6 7 Research has also shown that such population-wide movements or conflicts impact the mental health of the entire population, even including those who are not directly involved. 4 5 This is because other potentially traumatic events (PTE), such as unemployment, witnessing violence or even loss of property or loved ones, typically arise for different population strata regardless of actual participation in the disputes. 8 9 Therefore, the mental health status of the entire population of Hong Kong may be at risk of rapid deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Hou and Hall (2019), 2019's ongoing and large-scale protests in Hong Kong will significantly impact the mental health of the city's population. The likelihood of wide-spread posttraumatic stress has been identified in relation to previous protest movements in the region (Lau et al, 2017) and through recent empirical research (Lee, 2019). As the threat posed by the spread of the novel coronavirus (Covid-19) further disrupts day-to-day life in Hong Kong and across the globe, finding ways to support individual and community mental health becomes more urgent.…”
mentioning
confidence: 99%
“…However, under the broad category of psychological distress, anxiety and depression instead of posttraumatic stress symptoms might be more relevant to the people's experience during and after the Umbrella Movement (Hou et al, 2015;Lau et al, 2017;Ni et al, 2017). Therefore, in contrast to earlier work on the stress-based model of political extremism, psychological distress was operationalized as anxiety and depressive symptoms in this study.…”
Section: Socioeconomic Resources and Psychological Distressmentioning
confidence: 99%